Hero at large - Evanovich, Janet (Harper, 2010)
It seems like good luck when Ken Callahan stops to help single mom Chris Nelson with her car. Yet, after Ken moves into Chris' basement, a series of comic mishaps threatens to destroy their happiness. It'll take a meddlesome Aunt Edna, a ride on a Zamboni, and a genuine love of family to turn their luck around.